Der Tüftler der Inselärzte: Interview mit Jürg Küffer (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
Jürg Küffer, a trained precision mechanic, worked for Maurice E. Müller for 27 years from 1967. His work was extremely varied. He produced prototypes for medical instruments and devices, was involved in the development of hip joint prostheses, helped to compile and standardize surgical instruments, supported Müller's further training courses and accompanied him to operations abroad. He was inventive in solving the most diverse problems that arose in Maurice E. Müller's various companies. In 1967, the newly founded Pathophysiological Institute of the University of Bern and the Documentation Center of the Working Group for Osteosynthesis, which were both housed in the old Lindenhof Hospital, filled a jointly advertised mechanic position with Jürg Küffer. He then worked mainly for the newly founded Protek AG, but also helped other Insel doctors with the development of medical technology.